Strategi Pemasaran Pos Ketan Legenda 1967 Sudimoro Dalam Mempertahankan Bisnis Keluarga Pada Masa Pandemi Covid-19 Menggunakan Analisis SWOT - Adam Aufa Wijaya; Muhammad Ridwan Basalamah; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2023)
Abstract Pos Ketan Legenda 1967 Sudimoro is a branch of Pos Ketan Legenda based in Batu Tourism City, East Java which serves special food. The main food they sell is glutinous rice sprinkled with misis, cheese, soy powder, and others. This research aims to find out what marketing strategies they are doing in the face of the Covid-19 pandemic to maintain the family business they have been running since 1967. Because currently almost all business lines have suffered losses due to the Covid-19 pandemic.Using a sample of Pos Ketan Legenda 1967 Sudimoro and the research period in 2021-2022, the results showed that there is a strategy that can be done by the 1967 Sudimoro Legend Ketan Post by utilizing existing strengths and opportunities and minimizing weaknesses and threats. In this study also indicates that family businesses that have been established since 1967 such as Pos Ketan Legenda 1967 Sudimmoro certainly also have weaknesses and will continue to face threats around them. Not even now they are also facing the Covid-19 pandemic in order to maintain their business existence like other business. Keywords: Strategy, Marketing, Pos Ketan Legenda 1967 Sudimoro, SWOT Analysis